Therapeutic Effect Observations on Treatment of Urticaria with Acupuncture plus Garlic-partitioned Moxibustion - 耿萍 田玉华 林兆娟 王桂芬 汪司右 (Journal of acupuncture and tuina science, 2004)
Forty-six patients with intractable urticaria were treated by acupuncture plus garlic-partitioned moxibustion. The results were compared with those of simple acupuncture in a control group of 30 patients. The total effective rate were 91.3%, in the observation group and 73.3%, in the control group. It is showed that acupuncture plus garlic-partitioned moxibustion has a better effect on intractable urticaria than simple acupuncture.